Pannexin‐1 limits the production of proinflammatory cytokines during necroptosis - Douanne, Tiphaine; André‐Grégoire, Gwennan; Trillet, Kilian; Thys, An; Papin, Antonin; Feyeux, Magalie; Hulin, Philippe; Chiron, David; Gavard, Julie; Bidère, Nicolas (EMBO reports, 2019)
The activation of mixed lineage kinase‐like (MLKL) by receptor‐interacting protein kinase‐3 (RIPK3) controls the execution of necroptosis, a regulated form of necrosis that occurs in apoptosis‐deficient conditions. Active oligomerized MLKL triggers the exposure of phosphatidylserine residues on the cell surface and disrupts the plasma membrane integrity by forming lytic pores. MLKL also governs endosomal trafficking and biogenesis of small extracellular vesicles as well as the production of proinflammatory cytokines during the early steps of necroptosis; however, the molecular basis continues to be elucidated. Here, we find that MLKL oligomers activate Pannexin‐1 (PANX1) channels, concomitantly to the loss of phosphatidylserine asymmetry. This plasma membrane “leakiness” requires the small GTPase RAB27A and RAB27B isoforms, which regulate intracellular vesicle trafficking, docking, and fusion with the plasma membrane. Although cells in which PANX1 is silenced or inhibited normally undergo necroptotic death, they display enhanced production of cytokines such as interleukin‐8, indicating that PANX1 may tamper with inflammation. These data identify a novel signaling nexus between MLKL, RAB27, and PANX1 and propose ways to interfere with inflammation associated with necroptosis. Synopsis The activation of MLKL by RIPK3 controls the execution of necroptosis. During the early stages of necroptotic cell death, MLKL oligomers promote the activation of Pannexin‐1 channels, which constricts the production of proinflammatory cytokines. Pannexin‐1 is activated concomitantly to phosphatidylserine exposure during early steps of necroptosis. Activation of Pannexin‐1 by MLKL oligomers requires intracellular vesicles trafficking. Pannexin‐1 is dispensable for necroptotic cell death. Pannexin‐1 restrains the production of proinflammatory cytokines associated with necroptosis. Graphical Abstract The activation of MLKL by RIPK3 controls the execution of necroptosis. During the early stages of necroptotic cell death, MLKL oligomers promote the activation of Pannexin‐1 channels, which constricts the production of proinflammatory cytokines.